Structural and Optical Properties of Silicon Nanowire Arrays Fabricated by Metal Assisted Chemical Etching With Ammonium Fluoride - Gonchar, Kirill A.; Kitaeva, Veronika Y.; Zharik, George A.; Eliseev, Andrei A.; Osminkina, Liubov A. (Frontiers in Chemistry, 2019)
Here we report on the metal assisted chemical etching method of silicon nanowires (SiNWs) manufacturing, where the commonly used hydrofluoric acid (HF) has been successfully replaced with ammonium fluoride (NH4F). The mechanism of the etching process and the effect of the pH values of H2O2: NH4F solutions on the structural and optical properties of nanowires were studied in detail. By an impedance and Mott-Schottky measurements it was shown that silver-assisted chemical etching of silicon can be attributed to a facilitated charge carriers transport through Si/SiOx/Ag interface. It was shown that the shape of nanowires changes from pyramidal to vertical with pH decreasing. Also it was established that the length of SiNW arrays nonlinearly depends on the pH for the etching time of 10 minutes. A strong decrease of the tоtаl reflectance to 5-10 % was shown for all the studied samples at the wavelength less than 800 nm, in comparison with crystalline silicon substrate (с-Si). At the same time, the intensities of the interband photoluminescence and the Raman scattering of SiNWs are increased strongly in compare to c-Si value, and also they were depended on both the length and the shape of SiNW: the biggest values were for the long pyramidal nanowires. That can be explained by a strong light scattering and partial light localization in SiNWs. Hereby, arrays of SiNWs, obtained by using weakly toxic ammonium fluoride, have great potential for usage in photovoltaics, photonics, and sensorics.